Limitation of Authority of the BANI Arbitration Center in Government Construction Contract Disputes within the Electricity Sector - Pasaribu, David Mangara; Winada, Erik; Sungkara, Fajar; Sitompul, Wesleyzon; Wibowo, Singgar Mataniari; Hardjomuljadi, Sarwono; Sami’an, S. (CV. Social Politic Genius (SIGn), 2025)
Electricity infrastructure development is a national strategic sector directly intersecting with energy sovereignty and public interest. Therefore, construction contract disputes therein involve an intersection between private law and public law regimes. This research aims to critically analyze the basis of BANI’s legitimacy and the limitations of its authority in resolving government-construction contract disputes in the electricity sector. This is intended to guarantee the protection of energy sovereignty and the principle of legality in government administration. The research method applied is a normative juridical approach using the statute, conceptual, and case approaches, with a prescriptive, deductive syllogism analysis technique. The research results indicate that BANI’s legitimacy is derivative and limited. The arbitration institution lacks the adjudicative authority to review the validity of state administrative decisions or to set aside public electricity safety standards. These findings assert that BANI’s role must be reconstructed to remain within the corridor of purely commercial aspects without exceeding the administrative authority of public officials (ultra vires) in managing national strategic infrastructure. In conclusion, the limitation of arbitration authority is a manifestation of the limited delegation of authority doctrine, necessary to maintain state administration accountability while providing legal certainty for energy investment. This reconstruction makes a theoretical contribution by harmonizing party autonomy in civil law with legal sovereignty in the realms of Constitutional Law and State Administrative Law.